Science Embedded Vedic Philosophy and Educational Implications (Shanti Journal, 2023)
This study focuses on the Vedas, considering the earliest literary record of Hindu philosophy, a number of concepts related to science are found embedded  in the Vedic texts, and there are many its educational implications  for Nepal. The Veda is the original scripture containing spiritual as well as scientific knowledge encompassing all aspects of human life. The main aim of this study is to find out the certain concepts of science in Vedic scripture and see their educational implications. The scientific notion embedded in the Veda has been searched with a hermeneutic approach from Vedic hymns and commentaries. The ancient seers had recognised the scientific value of natural forces and they commended them as deities. Beyond this, they have formulated the universal law of heavenly forces and human beings. Moreover, the Veda  is accepted  as the most ancient and sacred text that has been guiding not only the cultural, religious and spiritual lives of Hindu people but also their thinking, inquiry and wisdom, encouraging its readers for social harmony, balance and multiplicity. And therefore, we recommend scientific ideas from the Vedic texts should be incorporated in the school curriculum of Nepal.